Tradisi Hizib Hirzul Jausyan di Pondok Pesantren; Sejarah dan Motif Pelaksanaannya - Kadi Kadi; Khairul Fitrin (Realita : Jurnal Penelitian dan Kebudayaan Islam, 2022)
This article aims to find out how the hizib hirzul jausyan tradition developed in Islamic boarding schools to achieve a problem goal, which includes the history of hizib hirzul jausyan and how the motifs used in the Al-Mahrusiyah Islamic boarding school with this type of research are descriptive analysis and use a phenomenological approach. By collecting data in the form of in-depth interviews with informants in the form of boarding school caregivers, students, and alumni of the Hidayatul Mubtadi-Ien Madrasah Parent (MHM) as teachers at the Dinah Putri Madrasah, and active advisors, in addition, researchers conducted observations and documentation. The data analysis process uses a flow model: data reduction, data presentation, and conclusions. The researcher aims to find out how we know the development of the hizib hirzul jausyan tradition which has developed from being certified to students until now making it a routine for students. In the motive of the implementation of the hiziban tradition, students are emphasized to take part in the reading of hizib hirzul jausyan with the aim that the students are motivated so that they can takarrub ilallah, in this case the students have been taught to always remember Allah.